In vivo antiplasmodial activity evaluation of the leaves of Balanites rotundifolia (Van Tiegh.) Blatter (Balanitaceae) against Plasmodium berghei - Asrade S; Mengesha Y; Moges G; Gelayee DA (Dove Medical Press, 2017)
Seyfe Asrade,1 Yohannes Mengesha,2 Getachew Moges,2 Dessalegn Asmelashe Gelayee1 1Department of Pharmacology, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, 2Department of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia Abstract: Balanites rotundifolia (BR) (Van Tiegh.) Blatter (Balanitaceae) has been used in Ethiopian folk medicine to treat malaria, despite the lack of scientific validation. Therefore, the present study was carried out to evaluate the antiplasmodial activity of 80% methanol leaf extract of BR in mice. Both the 4-day suppressive test and Rane’s test were employed. Three extract doses (BR100 mg/kg, BR200 mg/kg, and BR400 mg/kg/d) were given orally, and chloroquine was the standard drug administered through the same route. Outcome measures for evaluating antiplasmodial efficacy were parasitemia level, packed cell volume, survival time, and body temperature as well as body weight change. Moreover, preliminary phytochemical and acute toxicity studies were carried out. With the 4-day suppressive test, BR demonstrated dose-dependent significant reduction in parasitemia level at all test doses compared to the negative control: BR400 (67%, P<0.001), BR200 (42%, P<0.01), and BR100 (37%, P<0.05). With Rane’s test as well, BR significantly (P<0.001 for all test doses) reduced the parasitemia level by 38% (BR100), 45% (BR200), and 69% (BR400) in comparison to vehicle treatment. The crude extract was estimated to have oral median lethal dose higher than 2,000 mg/kg, and the presence of alkaloids and cardiac glycosides was confirmed. Therefore, this study for the first time validated the antiplasmodial activity of crude leaf extract of BR. Further investigations for isolating specific phytochemicals and elucidating mechanisms are needed to address the quest for novel antimalarial drugs. Keywords: antimalaria, antiplasmodial, Balanites rotundifolia, in vivo, Plasmodium berghei, traditional medicine